Partisipasi Masyarakat Dalam Meningkatkan Mutu Pendidikan Di Madrasah Tsanawiyah - Hurriyah, Nur Khulailatul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Schools are social institutions that cannot be separated from their community, on the other hand, society cannot be separated from schools. Because they both have interests. Schools as formal institutions entrusted with the mandate to educate, train and guide the nation's children (community), while the community is a stakeholder or user of educational services. The success of education is not only determined by the educational process in schools and the availability of facilities and infrastructure, but is also determined by the role of the family and community. Because education is a shared responsibility of schools, families and communities. So the community has a role to think about the implementation of education and participate in providing supervision in related schools. High community participation in schools is an indicator that school management is running well. When schools are side by side with both the community and parents, it will have a big impact on the progress of the school and will have a big influence on improving the quality in schools. Efforts to involve the community in improving the quality of education in schools can be taken by (1) conducting outreach to stakeholders, including school committees. (2) Involve formal leaders outside the school to participate in owning the school, because the progress and decline of educational institutions will also have an impact on the local community. (3) Showing the program directly, in addition to educating children, it can also show the achievements that have been achieved by students, teachers or school achievements as a whole.